Fisika Asyik Kegiatan Bongkar Pasang Melalui Aplikasi Phet Virtual Laboratory pada Listrik Dinamis - Harnofa Triza (Madaris: Jurnal Guru Inovatif, 2023)
This best practice paper aims to address the problem of minimal engagement in learning physics, assess the implementation of the assembly-disassembly learning approach using the PhET Virtual Lab application in enhancing physics learning outcomes, and describe the obstacles encountered in the implementation of the assembly-disassembly learning approach within the PhET Virtual Laboratory. The subjects of this study were the students of class XII IPA1 at MAN 1 Solok. The Fun Physics Learning activity involving assembly-disassembly through the PhET Virtual Laboratory application on dynamic electricity utilized the Inquiry Learning method, where students are guided to discover and establish the foundations of scientific thinking, allowing them to engage more in self-directed learning and develop creativity in problem-solving. The issue with physics learning, especially in class XII IPA at MAN 1 Solok, has been the monotonous methods of lectures, discussions, and assignments, resulting in low learning outcomes. This is primarily due to the difficulty students face in understanding concepts related to dynamic electricity. By applying the learning concept using the PhET application, students' engagement and learning outcomes have significantly improved. This is evident in the students' enthusiasm during the learning activities, such as creating circuits, assembling and disassembling new circuits with different components, and discovering new ideas through creativity. The problem-solving in physics learning, as seen from the achievement of learning outcomes, also showed an improvement. The overall learning outcomes of the students in class XII IPA1 have exceeded the minimum mastery criteria (KKM). Therefore, the assembly-disassembly learning activity through the PhET Virtual Laboratory application can be considered successful. This indicates that the concept is a successful and innovative approach to learning Abstrak Makalah best practice ini bertujuan untuk memecahkan masalah minimnya aktivitas belajar fisika, mengetahui pelaksanaan pembelajaran bongkar pasang pada aplikasi phet virtual lab dapat meningkatkan hasil belajar fisika serta mendeskripsikan hambatan dalam pelaksanaan pembelajaran bongkar pasang pada aplikasi phet  virtual laboratory . Sebagai Subjek dari penelitian ini siswa kelas XII IPA1 MAN 1 Solok. Pembelajaran Fisika Asyik kegiatan bongkar pasang melalui aplikasi Phet  virtual laboratory pada listrik dinamis ini menggunakan metode Inquiry Learning , dimana peserta didik dituntun untuk menemukan , menanamkan dasar-dasar berfikir ilmiah sehingga dalam proses pembelajaran  mereka lebih banyak untuk belajar sendiri, dapat mengembangkan kreativitas dalam memecahkan masalah. Permasalahan belajar Fisika khususnya pada kelas XII IPA MAN 1 Solok yang selama ini terlalu monoton dengan metode ceramah, diskusi dan penugasan, sehingga output dari pembelajaran masih rendah. ini disebabkaan tak lain karena kesulitan peserta didik dalam memahami konsep tentang Listrik Dinamis. Dengan menerapkan konsep pembelajaran menggunakan aplikasi phet ternyata dapat meningkatkan aktivitas dan hasil belajar peserta didik. Hal ini terlihat dengan begitu semangatnya peserta didik dalam kegiatan pembelajaran yang diberikan,membuat suatu rangkaian, membongkar dan memasang lagi rangkaian baru dengan komponen yang baru, dan menemukan hal yang baru dalam berkreativitas. Pemecahan masalah belajar fisika dilihat dari pencapaian hasil belajar juga terdapat peningkatan dalam hasil belajar. Pencapaian hasil belajar peserta didik kelas XII IPA1 secara umum telah melampaui pencapaian KKM. Maka kegiatan pembelajaran Bongkar Pasang melalui aplikasi phet secara Virtual Laboratory yang diterapkan dapat dikatakan berhasil. Artinya gagasan tersebut merupakan inovasi pembelajaran yang berhasil dengan baik